Pengaruh Motivasi kerja terhadap Kinerja PNS dengan Kepuasan Kerja sebagai Variabel Intervening - SABRINA SALSAHBILA PUTRI; Ristanti Akseptori; Irma Rustiani Aju (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
Human resources play a crucial role in achieving organizational goals, especially enhancing performance. This study focuses on the Department of Transportation in Gresik, aiming to examine the impact of work motivation on the performance of Civil Servants (PNS) while considering job satisfaction. Using purposive sampling, the research involved 61 PNS employees. A quantitative approach with explanatory research methods was applied, using questionnaires as the data collection tool. Simple linear regression and path analysis were used to test the hypotheses. The results show that work motivation has a positive impact on both the performance and job satisfaction of PNS employees. However, job satisfaction was not found to mediate the relationship between motivation and performance. The findings indicate that improved PNS performance is influenced by high work motivation, demonstrated through responsibility for core and additional tasks according to time targets and job descriptions. Supporting factors include satisfactory salaries, adequate facilities, and good working conditions.